Management of Reputational Risk: Problems with Definition and Measurement - Ewa Miklaszewska; Krzysztof Kil (Problemy Zarządzania, 2017)
Reputational risk is a relatively new concept, as it was not initially included in banking regulations. Only the post-crisis period brought about an increased interest in this type of risk. The purpose of this article is therefore to trace the sources and the consequences of reputational risk, in the context of the post-crisis drop in confidence in the banking sector. The paper focuses on the differences in the definition of the term and on methodological problems with its measurement. The empirical part proposes a new approach to measuring the reputational risk, on the basis of the reputational index constructed from the perspective of important stakeholders. The panel models analyze the impact of the index on bank performance in CEE.